Wide area monitoring, protection and control systems : the enabler for smarter grids - Vaccaro, Alfredo (IET power and energy series ;, 2016)
This book is designed to give electrical and electronic engineers involved in the design, operation and maintenance of electrical power networks, the knowledge and skills necessary to deploy synchronised measurement technology (SMT) in Wide Area Monitoring, Protection And Control (WAMPAC) applications.